ANALYSIS OF KANO STATE BUDGET FROM ISLAMIC ECONOMICS PERSPECTIVE 2007-2015 - Tasiu Tijjani Sabiu; Muhammad Bako (Universitas Airlangga, 2019)
Budgeting on conventional ground devises social goals by individualism, self-interest, and misplacement of priorities which creates and widens social inequality. On the other hand, Budgeting from Islamic economics perspective envisages and promotes equity, justice, and equality through mutual consultation and public maslaha and this is achieved by placing the budget in line with the goals of sharia which serves humanity better. The objective of the paper is to critically analyze Kano state budget from 2007 to 2015 based on Maqasid sharia framework. Thus, the paper is a conceptual analysis which relies on journal articles, books, conference proceedings and other relevant materials. The study reveals that the Kano state administration between 2007 to mid2011 incorporate sharia parameters fully into its budget policy and implementation while that of 2011 to mid-2015 partially observe some of the sharia parameters by emphasizing mostly on human capital development and capital project. Thepaper recommends that since Kano state is a sharia-compliant state and that the future administrations should fully envisage sharia parameters in its budget policies and implementation by placing more emphasis on and proper utilization of sharia supportive institutions or pillars such as Zakat and Hubsi commission, Hisbah board, sharia commission, coupled with productive and sustainable human and capital development projects.